Ki-67 and HER2-Negative Status as Predictive Factors for Recurrence and Progression in Breast Cancer: Implications for Treatment Strategies - Chemy Wiryawan Cahyono; Selamat Budijitno (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Breast cancer remains a significant health challenge, with HER2-negative subtypes representing a majority of cases. Ki-67, a marker of cell proliferation, has emerged as a potential prognostic factor in various cancers, including breast cancer. This study aimed to evaluate the association of Ki-67 expression and HER2-negative status with tumor characteristics, treatment response, and disease progression in breast cancer patients. Methods: A retrospective cross-sectional study was conducted at Dr. Kariadi General Hospital, Semarang, Indonesia. Data from 94 patients diagnosed with breast cancer were collected, including immunohistochemical profiles, HER2 status, Ki-67 index, treatment regimens, and tumor size. Statistical analysis was performed using SPSS version 25.0 for Windows. Results: The majority of patients (50%) presented with Luminal B-type breast cancer, and 77.7% had a Ki-67 index >20%. HER2-negative status was observed in 78.7% of patients. No significant correlation was found between HER2-negative status and the type of therapy given (p=0.131) or tumor size (p=0.467). Similarly, Ki-67 expression >20% did not correlate significantly with the type of therapy (p=0.070) or tumor size (p=0.156). Conclusion: While Ki-67 and HER2-negative status are recognized as important prognostic factors in breast cancer, this study did not find a significant association with treatment modalities or tumor size in the studied population. Further research with a larger sample size and longer follow-up is needed to validate these findings and explore the complex interplay of Ki-67, HER2 status, and other clinical variables in breast cancer progression.